Проблеми кодифікації законодавства про надра - Кірін, Роман Станіславович; Кирин, Роман Станиславович; Kirin, Roman (Одеса : Юрид. л-ра, 2014)
This article highlights for research of codifications problems of legislation about the bowels of the earth, to formulation, on beginning of ecology-economics doctrine, suggestions in context of Pandect of Ukraine about the bowels of the earth, and also his constituents – mountain and geological right.
Кірін Р. С. Проблеми кодифікації законодавства про надра / Р. С. Кірін // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 246-256.
Keywords: законодавство про надра; кодифікація; кодекс; надроправо; гірниче право; геологічне право; законодательство о недрах; кодификация; кодекс; недроправо; горное право; геологическое право; legislation about the bowels of the earth; codification; code; subsoil right; mountain right; geological right